A cardiac rehabilitation program increases the acute respond of endothelial progenitor cells after maximum exercise in patients with chronic heart failure. (25th November 2020) - Kourek, C; Karatzanos, E; Delis, D; Alshamari, M; Linardatou, V; Psarra, K; Dimopoulos, S; Pittaras, T; Vasileiadis, I; Nanas, S
Abstract: Background: Chronic heart failure (CHF) remains a leading cause of morbidity and mortality and it is characterized by vascular endothelial dysfunction. During the last decades, endothelial progenitor cells (EPCs) are being used as an index of the endothelium restoration potential, therefore reflecting the vascular endothelial function. Exercise training has been shown to stimulate the mobilization of EPCs at rest in CHF patients. However, the effect of exercise training on the acute respond of EPCs after maximum exercise in CHF patients remains unknown. Purpose: The purpose of the study was to assess the effect of a cardiac rehabilitation (CR) program on the acute respond of EPCs after maximum exercise in patients with CHF. Methods: Forty-four consecutive patients (35 males) with stable CHF [mean±SD, Age (years): 56±10, BMI (kg/m 2 ): 28.7±5.2, EF (%): 33±8, Peak VO2 (ml/kg/min): 18.4±4.4, Peak work rate (watts): 101±39] enrolled a 36-session CR program based on high-intensity interval exercise training. All patients underwent an initial symptom limited maximal cardiopulmonary exercise testing (CPET) on an ergometer before the CR program and a final maximal CPET after the CR program. Venous blood was drawn before and after each CPET. Five circulating endothelial populations were identified and quantified by flow cytometry; CD34+/CD45-/CD133+, CD34+/CD45-/CD133+/VEGFR2, CD34+/CD133+/VEGFR2, CD34+/CD45-/CD133- and CD34+/CD45-/CD133-/VEGFR2. EPCs values are expressed as cells/million enucleated cells in medians (25th-75th percentiles). Results: The acute mobilization of EPCs after the final CPET was higher than after the initial CPET in 4 out of 5 circulating endothelial populations. Most specifically, difference of the acute mobilization of CD34+/CD45-/CD133+ cells [initial CPET: 25 (15–46) vs final CPET: 49 (26–71), p=0.002], CD34+/CD45-/CD133+/VEGFR2 cells [initial CPET: 3 (2–5) vs final CPET: 8 (5–12), p<0.001], CD34+/CD45-/CD133- cells [initial CPET: 129 (52–338) vs final CPET: 250 (129–518), p=0.03] and CD34+/CD45-/CD133-/VEGFR2 cells [initial CPET: 2 (1–4) vs final CPET: 6 (3–9), p<0.001] increased after the final CPET. The acute mobilization of CD34+/CD133+/VEGFR2 cells [initial CPET: 3 (−1–7) vs final CPET: 5 (0–15), p=0.441] did not differ between the 2 CPETS. Conclusion: A 36-session cardiac rehabilitation program increases the acute respond of endothelial progenitor cells after maximum cardiopulmonary exercise training in patients with chronic heart failure, therefore indicating the beneficial effect of exercise training on the vascular endothelial function. Funding Acknowledgement: Type of funding source: Public grant(s) – EU funding. Main funding source(s): Co-financed by Greece and the European Union (European Social Fund- ESF) through the Operational Programme "Human Resources Development, Education and Lifelong Learning" in the context of the project